Analysis of Rainfall Data for Soil Conservation and Crop Planning - Bhatia, K. S.; Gupta, R. N.; Singh, R. S. (Indian Forester, 1975)
Twenty years rainfall data of Rehmankhera (Lucknow) have been analysed in this paper. Mean monthly, percent distribution, expected rainfall at different percent chance, frequency of continuous dry days, daily maximum rainfall, variability of annual rainfall, its distribution and trend have been presented. Monthly data showed a great variability in rainfall. About 76% of rainfall was concentrated in monsoon season. Rabi season received only 9.9% rainfall which will cause failure in Rabi season crop without adequate measures for conserving moisture and without providing irrigation facilities in the region. Weekly rainfall has great importance in crop planning than monthly seasonal or annual rainfall. Probability and frequency analysis of rainfall data have been done which provides more useful tool for application of such data. One year out of every ten years has been found to be drought year.